2018
DOI: 10.4103/joacp.joacp_198_18
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of femoral nerve block with adductor canal block following total knee arthroplasty: A systematic literature review

Abstract: Background:Patients undergoing total knee arthroplasty suffer from moderate-to-severe postoperative pain resulting in immobility-related complications and prolonged hospitalization. Femoral nerve block is associated with reduction in the quadriceps strength and increasing incidence of falls. Adductor canal block has been shown to be as effective as femoral nerve block without causing quadriceps weakness.Objectives:To compare outcomes of studies comparing adductor canal block and femoral nerve block in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…There is concern among surgeons and physiotherapists that continuous femoral nerve block (FNB) may hamper motoric function, thereby leading to delayed ambulation and increasing risk of falls (22). As a consequence, ACB has been promoted in order to provide adequate analgesia with less quadriceps weakness compared to femoral block (23,24). However, Schwenk and Gandhi 25focused on conclusions drawn from dynamometer data and emphasized that differences in motoric function between ACB and FNB were significant only during the first 8 postoperative hours, whereas fall accidents mostly occurred on the second postoperative day.…”
Section: Motoric Function and Adductor Canal Blockmentioning
confidence: 99%
“…There is concern among surgeons and physiotherapists that continuous femoral nerve block (FNB) may hamper motoric function, thereby leading to delayed ambulation and increasing risk of falls (22). As a consequence, ACB has been promoted in order to provide adequate analgesia with less quadriceps weakness compared to femoral block (23,24). However, Schwenk and Gandhi 25focused on conclusions drawn from dynamometer data and emphasized that differences in motoric function between ACB and FNB were significant only during the first 8 postoperative hours, whereas fall accidents mostly occurred on the second postoperative day.…”
Section: Motoric Function and Adductor Canal Blockmentioning
confidence: 99%
“…123,124 This technique targets the saphenous nerve, articular branches of the obturator nerve, medial retinacular nerve, and the nerve to the vastus medialis. 125 A recent systematic review by Karkhur et al did not find any difference in pain scores or opioid consumption between FNB or ACB following TKA. 125 While nerve blocks are commonly employed in multimodal pain management regimens, the ERAS Society does not recommend them as an essential component of multimodal analgesia following TKA.…”
Section: Orthopedic Reviewsmentioning
confidence: 95%
“…125 A recent systematic review by Karkhur et al did not find any difference in pain scores or opioid consumption between FNB or ACB following TKA. 125 While nerve blocks are commonly employed in multimodal pain management regimens, the ERAS Society does not recommend them as an essential component of multimodal analgesia following TKA. 65 Additionally, local infiltration analgesia (LIA) can be used as an alternative or as an adjunct to nerve blocks, and was first described by Kerr et al in 2008.…”
Section: Orthopedic Reviewsmentioning
confidence: 95%
“…In TKA, the use of blocks is more common and adductor canal blocks (ACBs) have become increasingly popular over FNBs because they preserve quadriceps strength better, thus preventing falls and facilitating early mobilization 99,105-107 . In addition, Li et al showed significantly better pain scores with ACBs over FNBs in a meta-analysis of 8 RCTs 108 .…”
Section: Analgesia: Local Anestheticsmentioning
confidence: 99%